Polymer science - Gowarikar, V. R. (New Age International, 2015)
Offers basic coverage of the chemistry, physics, and techniques of polymer science. While avoiding detailed mathematics, it presents topics in a logical manner using examples and analogies which make even difficult abstract concepts understandable. Topics include foundation chemistry; weight, size, chemical and geochemical structure of polymer molecules; crystallinity in polymers, co-polymers, and polymer solutions. The text is designed particularly for the uninitiated who need to move quickly to a level from which to absorb the more advanced literature in the field. Worked-out examples, easily followed lab procedures on the synthesis of polymers, tables, and illustrations are included